Understanding Program Complementarities: Estimating the Dynamic Effects of Head Start with Multiple Alternatives - Marc K. Chan; Antonio Dalla-Zuanna; Kai Liu (Institute of Labor Economics (IZA), 2024)
We use experimental data from the Head Start Impact Study to examine the effects of childcare program pathways on cognitive outcomes. Using a sequential choice model with state dependence and dynamic selection, we identify and estimate joint returns and complementarities across skill investment programs. Our results indicate differential returns by the sequencing of program participation, and support engaging low-ability children with prolonged center-based care and high-ability children with some home care. We then use a dynamic structural model to evaluate a counterfactual reform which limits children to one year of Head Start, showcasing the importance of accounting for dynamic behavior.
Keywords: 330